A Diagnostically Challinging Case of Primary Thyroid Kappa-restricted Plasma Cell- Rich Hematolymphoid Neoplasm with Focal Plasmablastic Differentiation. (28th October 2020) - Haleema, S O; Akbar, S; Rowley, E; Polski, J M; Mneimneh, W
Abstract: Introduction/Objective: Most low-grade B-cell lymphomas of the thyroid are extranodal marginal cell lymphomas (MZL) and may exhibit focal plasma cell differentiation (PCD). PCD could occasionally be extensive, mimicking a true plasma cell neoplasm (PCN). PCN of the thyroid are extremely rare, representing either a component of plasma cell myeloma (PCM), or a primary thyroid extraosseous plasmacytoma (EOPC). We present a case of primary thyroid plasma cell (PC)-rich neoplasm with considerable diagnostic challenge. Methods: A 46-year-old male underwent total thyroidectomy for hypothyroidism and compressive symptoms. Microscopically, sheets and nodules of PC with focal plasmablastic features were demonstrated in a background of fibrosing chronic thyroiditis. One benign perithyroidal lymph node was seen. The differential diagnosis included B-cell neoplasm with extensive PCD (ie, MZL or lymphoplasmacytic lymphoma) and PCN. Results: Immunohistochemically, the PCs were positive for CD79a, MUM1, BCL2 and IgM with Kappa light-chain restriction and partial CD138 expression, and negative for CD20, PAX5, HHV8, Cyclin-D1, SOX11, CD117 and IgG. EBER was negative. Rare reactive-appearing B-cell aggregates with associated T-cells were noted. FISH for API/MALT1-fusion t(11;18) and PCR for MYD-88 mutation were negative. However, polysomy 18 (seen in 15–33% of B-cell lymphomas, including MZL) was detected. Serum proteins and PCM workup were negative. The findings were consistent with primary thyroid Kappa-restricted PC-rich neoplasm. While the absence of detectable B-cell neoplastic component was suggestive of EOPC, the diagnosis of MZL with extensive PCD was favored due to the thyroid involvement in a background of thyroiditis, absence of lymph node involvement, detection of polysomy 18, and absence of MYD-88. Follow-up of the patient was thought to be most reasonable. Conclusion: Plasma cell-rich hematolymphoid neoplasms of the thyroid may cause a considerable diagnostic challenge. Differentiating between B-cell lymphomas with extensive PCD and PCN may be difficult or even impossible by morphology alone. Additional ancillary tests may be necessary.